Documenting Some Species of Bats in the Central and Coastal Regions of Syria - Al- Ramadan, Yara; Ibrahim, Nahla; Al- Omar, Anouar (International Journal of Scientific Research in Biological Sciences, 2020)
We have studied and documented Six Species of bats in the central region of Syria (Eastern, and Western Homs countrysides) and some areas of the Syrian coastal region (Draykish, Safita and Ash Shaykh Badr).These Species are: Roussettus aegyptiacus, Myotis myotis, Myotis blythii, Pipistrellus kuhlii, Pipistrellus savii, Rhinolophus ferrumequinum. The Species Pipi strellus savii has been recorded for Syria for the first time in Slanfah – Lattakia on 2/10/2018. Pipistrellus kuhlii has been recorded in Sukkarah (eastern Homs countryside) on 16/7/2017 and Ash Shaykh Badr (Tartus) on 19/8/2017, Rhinolophus ferrumequinum has been recorded in Fajlit (Draykish) on 30/9/2017 and Al-Zahabiya (Shin district west Homs countryside) on 1/8/2017. Myotis myotis, Roussettus aegyptiacus have been recorded in in Al-Dawwar cave - Kafr Sanif (Safita – Tartus) on 5/10/2017 and on 14/7/2018, Myotis plythy has been recorded Which Myotis myotis, Roussettus aegyptiacus in same cave on 14/7/2018, the morphometric measurements of these Species have been taken and classified and compared with previous studies in Syria and Egypt.